WWOX P47T partial loss-of-function mutation induces epilepsy, progressive neuroinflammation, and cerebellar degeneration in mice phenocopying human SCAR12. (April 2023) - Hussain, Tabish; Sanchez, Kevin; Crayton, Jennifer; Saha, Dhurjhoti; Jeter, Collene; Lu, Yue; Abba, Martin; Seo, Ryan; Noebels, Jeffrey L.; Fonken, Laura; Aldaz, C.Marcelo
Abstract: WWOX gene loss-of-function (LoF) has been associated with neuropathologies resulting in developmental, epileptic, and ataxic phenotypes of varying severity based on the level of WWOX dysfunction. WWOX gene biallelic germline variant p.Pro47Thr (P47T) has been causally associated with a new form of autosomal recessive cerebellar ataxia with epilepsy and intellectual disability (SCAR12, MIM:614322). This mutation affecting the WW1 protein binding domain of WWOX, impairs its interaction with canonical proline-proline-X-tyrosine motifs in partner proteins. We generated a mutant knock-in mouse model of Wwox P47T mutation that phenocopies human SCAR12. Wwox P47T/P47T mice displayed epilepsy, profound social behavior and cognition deficits, and poor motor coordination, and unlike KO models that survive only for 1 month, live beyond 1 year of age. These deficits progressed with age and mice became practically immobile, suggesting severe cerebellar dysfunction. Wwox P47T/P47T mice brains revealed signs of progressive neuroinflammation with elevated astro-microgliosis that increased with age. Cerebellar cortex displayed significantly reduced molecular and granular layer thickness and a strikingly reduced number of Purkinje cells with degenerated dendrites. Transcriptome profiling from various brain regions of WW domain LoF mice highlighted widespread changes in neuronal and glial pathways, enrichment of bioprocesses related to neuroinflammation, and severe cerebellar dysfunction. Our results show significant pathobiological effects and potential mechanisms through which WWOX partial LoF leads to epilepsy, cerebellar neurodegeneration, neuroinflammation, and ataxia. Additionally, the mouse model described here will be a useful tool to understand the role of WWOX in common neurodegenerative conditions in which this gene has been identified as a novel risk factor. Highlights: Germline WWOX P47T partial loss-of-function mutation has been associated with autosomal recessive spinocerebellar ataxia with epilepsy and intellectual disability (SCAR12, MIM:614322). We generated a knock-in mouse model of Wwox P47T hypomorphic mutation that phenocopies human SCAR12 and confirming this mutation impairs the interaction function of Wwox. Wwox P47T/P47T mice exhibit epilepsy, abnormal social behavior, and poor motor coordination. Wwox P47T/P47T brains show progressive neuroinflammation and evidence of cerebellar hypoplasia and Purkinje cells degeneration. This mouse model will be a useful tool to understand the role of WWOX in common neurodegenerative conditions in which this gene has been identified as a novel risk factor.